Warfarin or non-Vitamin K antagonist oral anticoagulants: Navigating the choice of oral anticoagulant drugs in the COVID-19 pandemic era - Heng Cai; Xin Zhou; Qing Yang (Cardiology Plus, 2020)
Emerging evidence indicates that thromboembolic complications are a key determinant of inhospital mortality of patients with COVID-19. Prophylactic anticoagulation therapy is an important component of inhospital management of patients with COVID-19. Considering that millions of patients worldwide are prescribed oral anticoagulation therapy, herein, we summarize the pros and cons of non-Vitamin K antagonist oral anticoagulants (NOACs) and warfarin, in terms of pharmacodynamics, and therapeutic efficacy and adverse effect monitoring in the context of the global pandemic of COVID-19. Despite a lack of evidence from high-quality randomized trials, an NOAC, rather than warfarin, would be a scientifically reasonable treatment option for patients with COVID-19 in the outpatient setting.